Bradley and Lonergan’s Relativist - Teske, Roland J. (Philosophy & theology, 1990)
Bernard Lonergan contrasts his account of judgment with that of the relativist. This paper points out how Lonergan’s characterization of the relativist account of judgment closely resembles the account of judgment that F. H. Bradley had given. Furthermore, the paper points to areas of commonality between Lonergan and Bradley with regard to human knowing. Despite their similarities, however, Lonergan’s account of judgment clearly distinguishes his theory of knowing from anything Iike Bradley’s idealism.